Immune-Mediated Inflammation: Human T CD4 Helper Lymphocyte Diversity and Plasticity in Health and Disease - Kolliker Frers, Rodolfo Alberto (2019)
The CD4+ T helper (Th) cells have a critical role in organizing the adaptive immune response. The emerging cells of the differentiation after the immune synapse produce helper T cell subpopulations that activate, suppress, or regulate the immune response upon interaction with varying immune cells. There are two main Th cell functional categories: the “effector cells” and the “regulatory T cells.” Classic T helper lymphocytes can also be distinguished by their lineage according to the developmental microenvironment, the expression of cell adhesion-homing receptors, the profile of cytokines they are exposed to, and the involved transcription factors. Traditionally, the CD4+ and CD8+ phenotypes have been considered as helper and cytotoxic/suppressor T lymphocytes, respectively. Currently, the distinction is little rigorous. The immune response is exceedingly complex beyond the classic Th1 and Th2 effector cells’ involvement, and other populations of helper T lymphocytes like the Th17, Tfh, Th22, and Th9 lymphocytes have been phenotypically characterized. These lymphocytes also participate in the pathogenesis of several immune-mediated inflammatory disorders. Here, we revisit and discuss the essential aspects of the state of the art regarding phenotypic diversity and plasticity of TCD4 cells in the T lymphocyte repertoire frame and their potential implication in human inflammatory diseases.